La Brisa Sunday market: A vibrant fusion of Balinese tradition, sustainability, and global trends in tourism experiences - Arjana, I Wayan Basi; Gede Putra Yudistira, Cokorda; Kasiani, Kasiani; Mudana, I Wayan (Yayasan Mitra Persada Nusantara, 2025)
La Brisa was launched in 2017 in Canggu, Bali. However, the place has gained popularity due to the beachside setup. Among the attractions which open its doors to guests is the namely La Brisa Sunday Market with multicultural shops and the social area where guests meet while strolling the area with the eco-friendly products and goods, world-class cuisine, and handmade products offered at the market. Thus, how La Brisa enchant diversification, Innovation, and sustainable development to encourage local people business and interpenetration between cultures? In this paper the author is looking at why the location is a favorite amongst visitors and how it manages to make the Balinese culture relevant to the international market while at the same time creating a unique theme that both is meaningful and enjoyable. For this research, observations of the market were conducted, the authors conducted interviews with vendors, visitors, and La Brisa employees to gain first-hand experience, and they collected articles from online sources and populated a database from the market. Our interviews gave information about participant demographics, their purpose of coming to the market, as well as their perception towards it, while field trips gave a live perspective on the actual happening of the market environment. La Brisa Sunday Market can be ‘an exemplification of a successful neighborhood project that had purchased the good representation of people.’ In essence, La Brisa Sunday Market exemplifies how community, business, and culture can coexist harmoniously, offering a model for sustainable and inclusive neighborhood projects.